CODESRIA Bulletin Online, No. 21, July 2021 - Rebutting the Response to Amoah’s ‘Ghana’s Democracy and the 2020 Election: Signs of a Fading Promise?’ - Amoah, Lloyd (CODESRIA Bulletin, 2021)
Introduction This piece comes as a response to a putative rebuttal1 to my article (Amoah 2021),2 authored by Nene-Lomotey Kuditchar. As disputatio goes, such a rebuttal is healthy for the CODESRIA Bulletin, where any ambiguities and distortions that an article presents may be clarified. Beyond these, perspectives that might have been missed may be proffered and thus enlighten us all. My candid view, though, is that Kuditchar’s response in question does not meet the aforementioned criteria. On the contrary, Kuditchar constructs a grotesque straw man and then proceeds to bayonet same with all the cerebral force he can muster. I will proceed to show this in the subsequent sections. Building Straws for the Straw Man Argument Straw man arguments tend to totally miss the point. They do so by heading off in argumentative directions that have scant bearing, at best, or none at all, at worst, on the matter at hand. Having made this move, such arguments proceed to engage with fresh premises and conclusions with solipsistic glee and narcissistic abandon. Let us see how Kuditchar’s response sets the stage for such an argument. The author misses my periodisation entirely. My time frame for analysis is the Fourth Republic, which in temporal terms took off on 7 January 1993 when the 1992 Constitution technically became operable. My article did not seek in any way to engage in a longue durée analysis harking back to Ghana’s engagement with liberal democracy in recent times nor its democratic constitutional engineering going back to the 1850s. In mentioning 1966, which the author refers to (Kuditchar 2021: 62), I was simply elucidating the explanandum (Amoah 2021: 37) of the Fourth Republic and its material deficits, which I had highlighted in the sentence preceding the one bearing the date 1966. The other key straw is the confounding mischaracterisation of my reference to the peaceful transition from one administration to another in the Fourth Republic. By peaceful transition I meant the processes and acts of transfer of power from one administration to another after elections. How this reference morphs into my claim that there was no violence and loss of life before and during elections involving the New Patriotic Party (NPP) and the National Democratic Congress (NDC) is a mystery only Kuditchar can help us resolve. He is so sure about this humouring transmogrification that he goes on to provide a laundry list of violence (Kuditchar 2021: 61–62) to underscore his self-induced misdirection. Welcome the Straw Man Argument In my considered view, Kuditchar is captivated by the idea of the consolidation of Ghana’s democracy. There is nothing wrong at all with that. All he needed to do, then, was to write an article on that and present it to this esteemed academic outlet for consideration instead of unwittingly battling ghosts and phantoms so publicly. The word ‘consolidation’ appears twice (Kuditchar 2021: 62) in his work. I therefore assert that democratic consolidation is the central core of his argument. He proceeds to show why democratic consolidation matters to him by pointing out manifestations of it: the presence and activities of civil society actors; what he describes as ‘democratic self-correcting capacity’; ‘splitting parliamentary seats evenly between the two parties’. Clearly, this is the gravamen of his piece to which he gives his best intellectual shots alas and to which he should have stuck. Inattention and Contradictions Attacking the Straw Man meant that when Kuditchar attempts to tackle my claim that the Ghanaian Fourth Republic may not be living up to its material rationale (on account of pervasive partisanship and, with it, the winner-takes-all phenomenon) he is blissfully inattentive and masterfully contradictory. Kuditchar happily cites an Afrobarometer study indicating that 79 per cent of Ghanaians are willing to honour their tax obligations to the state even though 61 per cent do not know what the revenue raised is used for. He utilises this point to indicate that Ghanaians still maintain fiduciary trust in the Ghanaian state. In an intriguingly contradictory statement, Kuditchar, before laying down the fiduciary argument, confirms the material deficit charge (which 61 per cent of Ghanaians affirm) that I lay against the Fourth Republic. Hear him: ‘This finding suggests … unmet material needs may be a source of frustration to the electorate’ (Kuditchar 2021: 62). One would have thought that he also would be worried that 61 per cent of Ghanaians surveyed have no idea where their money is going, which I raised in my article to underscore the elusive realisation of the material rationale. One has to be truly inattentive to miss this. It seems to point to a classic case of talking from both sides of one’s mouth. To be clear, though, my article did not question the Ghanaian state’s developmentalist role. On the contrary, it took issue with the seeming absence of developmentoriented politicos under the Fourth Republic. Kuditchar attempts to clobber my argument about pervasive partisanship and makes a hash of it. His mode of attack is to lean on Chazan (1982) and Boahen (1996) to claim that the party duopoly in Ghana3 has effectively exorcised ethnopartisanship. This claim definitely is open to debate (Sefa-Nyako 2020; Arthur 2009; Graham and Faanu 2017) that argues against the seemingly indubitable conviction Kuditchar has of partisanship’s apparent exorcism. I invite Kuditchar to see the parties as the new tribe to which some Ghanaians are totally beholden; this is the point I tried to put across in my article. At the time of writing this piece, the horrors of this neotribalism have played out once again. An NPP activist, Ibrahim Mohammed, has been brutally murdered, allegedly by his own party members, for daring to criticise the ruling government on social media.4 Regarding my analysis of the winner-takes-all syndrome, Kuditchar (2021: 63) labels it a ‘suggestion’. This is actually, contrary to his assertion, an empirical fact about which the same Ghana Center for Democratic Development (CDDGhana) that Kuditchar quotes liberally in his response was concerned enough to write about.5 It will be useful to quote two notable Ghanaian scholars linked to the CDD-Ghana and their take on this (Gyimah-Boadi and Prempeh 2012: 101): Ghanaian democracy is far messier than is typically portrayed; it has been described as ‘factional,’ ‘venomous,’ and ‘acrimonious.’ Political contestation between the NPP and NDC rarely focuses on principled policy-based disagreement over concrete issues. Personal attacks and ad hominem accusations are more common. Every matter of significant public interest or controversy, even the fratricidal killing of a local chief, is seized upon by the two rival parties and turned into an occasion for political grandstanding and gamesmanship. Underlying this increasingly incendiary tone of contemporary Ghanaian politics is the winnertakes-all, zero-sum character of the country’s political system. (emphasis mine) Conclusion It is instructive that Kuditchar points to what he describes as ‘the democratic social contract enshrined in the 1992 Constitution’. If he were paying attention to the literature on social contract theory it would be clear to him that enshrinement is not enough, nor are pious platitudes. No wonder this theory has been subjected to bruising critique on account of its descriptive (not normative) aspects in Afro-modern political thought (Mills 1997). The upshot of this is that facile moves encapsulated in so-called periodic self-correction artifices, of which Kuditchar seems enamoured, may not lead to the kind of social justice Ghanaians deserve. As the practice of democracy in Ghana approaches its thirty-year mark (a generation) in 2023, the choice is stark: to raise substantive or, instead, peripheral questions to address its shortcomings. I chose the former. Notes https://www.codesria.org/spip. php?article3187&lang=en. https://www.codesria.org/spip. php?article3139&lang=en. To be sure, the 1992 Constitution outlaws ethnopolitics under Article 55(4). The Political Parties Act, 2000 (Act 574), Section 9 underscores this. But there are the laws and then there is reality. https://www.myjoyonline.com/social-media-reacts-to-death-ofactivist-protest-in-ejura/ http://cddgh.net/publications/Constitutional-Review-Series/ No8-Ghanas-WinnerTakesAllPolitics-Leading-Causes-and-Proposed-Constitutional-Remedies